THE RELATIONSHIP OF FoxP3+ T REGULATORY CELLS TO DISEASE ACTIVITY AND ANTIBODY LEVELS IN EARLY RHEUMATOID ARTHRITIS - A. S. Avdeeva; Yu. P. Rubtsov; D. T. Dyikanov; T. V. Popkova; E. L. Nasonov (Научно-практическая ревматология, 2017)
Objective: to analyze the relationship of the count of FoxP3+ T regulatory cells (Tregs) to the clinical and laboratory parameters of disease activity and the levels of antibodies in a group of patients with early rheumatoid arthritis (RA).Subjects and methods. The investigation enrolled 45 patients with early RA (2010 ACR/EULAR criteria) who had not previously received treatment with methotrexate, including 39 women; median age was 52.0 [32.5; 57.5] years; disease duration, 5 [4; 6] months, DAS28 5.01 [4.18; 5.8]; 71.1% of the patients were rheumatoid factor (RF) positive and 88.9% were anti-cyclic citrullinated peptide positive. The relative and absolute counts of Treg (FoxP3+CD25+; CD152+surface; CD152+intracellular; FoxP3+CD127-; CD25+CD127-; FoxP3+ICOS+; FoxP3+CD154+; FoxP3+CD274+) were measured by immunofluorescence staining and multicolor flow cytometry. A control group consisted of 20 healthy donors who were matched for sex and age with the examined patients.Results and discussion. DАS28 was high, moderate, and low in 22 (48.9%), 20 (44.4%), and 3 (6.7%) patients, respectively. As compared with the healthy donors, the patients with early RA were observed to have lower values in the percentage of FoxP3+CD25+ cells, in the percentage and absolute count of FoxP3+ICOS+ cells, in the percentage and absolute count of FoxP3+CD154+ and FoxP3+ CD274+ T cells; p<0.05 in all cases. Negative correlation was recorded between the percentage of FoxP3+CD25+ and C-reactive protein (CRP) (r=-0.4); that of CD152+intracellular and DAS28 (r=-0.35), ESR (r=-0.46), CRP (r=-0.54); that of FoxP3+CD127 and CRP (r=-0.42); that of CD25+CD127 and DAS28 (r=-0.38), SDAI (r=-0.41), CDAI (r=-0.36), ESR (r=-0.39), CRP (r=-0.47); p<0.05 in all cases.The patients who were seronegative for RF were found to have higher values in the percentage of CD25+CD127, in the percentage and absolute count of Foxp3+CD154+ and Foxp3+CD274+ T lymphocytes.Conclusion. The given data may indicate that the count and functional activity of Treg were decreased in early RA, which is associated with higher disease activity, the systemic manifestations of the disease and which is also accompanied by antibody hyperproduction.